(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
A method has been developed for the selective thermocatalytic determination of hydrocarbons, based on the use of sensitive elements (measuring and compensation) of sensors containing catalysts with inadequate activity to the components of the gas mixture. The influence of various factors on the metrological and operational parameters of the thermocatalytic sensors of hydrocarbons was studied. Thermo catalytic gas analyzers have been created that provide the selective determination of hydrocarbons (gasoline vapors, diesel fuel, etc.) in a wide range of their concentrations. The developed analyzers are characterized by high sensitivity, selectivity, and speed.